Superdialectos, dialectos y subdialectos del español de Colombia - Bonilla, Johnatan E. (2023)
The objective of this work is to offer a proposal for the dialectal classifica-tion of Colombian Spanish based on the dialectometric analysis of lexical data from the Atlas Lingüístico-Etnográfico de Colombia (ALEC). The study involvedtwo hundred lexical maps from the ALEC which were randomly selected and processed in the Gabmap dialectometric analysis software. The similarity measure used was the Relative Index of Identity (Goebl 1984) and the visualization was carried out using the fuzzy clustering method. Based on the analysis of the results, the division of Colombian Spanish into three superdialects is proposed: central-eastern Andean, central-western Andean and Coastal. The Andean superdialects are divided from north to south (taking into account the dialect continuum) into high, middle and low dialects, while the Coastal superdialect distinguishes Caribbean and Pacific varieties. Finally, twenty-two subdialects corresponding to specific regions of the country are presented, along with their respective municipalities.